Utilization of Online Learning Platforms to Improve Elementary School Teachers’ICT Competence: Pemanfaatan Platform Pembelajaran Daring Untuk Meningkatkan Kompetensi TIK Guru SD - Dodiet Enggar Wibowo; Anwar Senen; Ali Mustadi; Muhammad Nur Wangid; Nita Pratiwi; Miftakhuddin (Yayasan Ahmar Cendekia Indonesia, 2022)
To support Learning From Home (BDR), elementary school teachers in Kapanewon Kokap, Yogyakarta, have low ICT skills. This service seeks to improve the ICT competence of elementary school teachers in Kapanewon Kokap. This service activity is carried out in an action research design that adopts a workshop procedure. This activity is divided into three stages. In the first and second stages, classical discussions (supervision) were carried out which were guided by professionals. The topics of discussion are various online learning platforms that can be used by participants. In the third stage, participants practice developing and utilizing online learning platforms, then presenting them to supervisors and other participants. The results of this service activity indicate a significant increase in ICT competence, both at the level of knowledge acquisition, knowledge deepening, and knowledge creation. This can be seen from the increase in the score of the post-test results. This increase can facilitate the implementation of their obligations to provide appropriate education and teaching according to the characteristics of today's children. Abstrak Untuk mendukung Belajar Dari Rumah (BDR), guru SD di Kapanewon Kokap, Yogyakarta, memiliki keterampilan TIK yang rendah. Pengabdian ini berusaha meningkatkan kompetensi TIK guru SD di Kapanewon Kokap. Kegiatan pengabdian ini dilaksanakan dalam desain penelitian tindakan yang mengadopsi prosedur workshop. Kegiatan ini terbagi ke dalam tiga tahap. Pada tahap pertama dan kedua, dilakukan diskusi klasikal (supervisi) yang dibimbing oleh profesional. Topik diskusi adalah berbagai platform pembelajaran online yang dapat digunakan oleh peserta. Pada tahap ketiga, peserta berlatih mengembangkan dan memanfaatkan platform pembelajaran online, kemudian mempresentasikannya kepada supervisi dan peserta lainnya. Hasil kegiatan pengabdian ini mengindikasikan adanya peningkatan kompetensi TIK yang signifikan, baik pada tingkat perolehan pengetahuan, pendalaman pengetahuan, maupun penciptaan pengetahuan. Hal ini terlihat dari peningkatan skor hasil post-test. Peningkatan tersebut dapat mempermudah pelaksanaan kewajiban mereka untuk memberikan pendidikan dan pengajaran yang tepat sesuai dengan karakteristik anak-anak saat ini.